Effects of the Lubo cervical collar on airway patency in awake adults – A magnetic resonance imaging study - Jaga, Rudhir (Department of Anaesthesia and Perioperative Medicine, 2023)
Introduction: Intended for use by prehospital first responders, the Lubo TM cervical collar is an adjustable, radiolucent, single-use device that incorporates a mechanical jaw thrust mechanism. The combination enables non-invasive airway management in cases of trauma where cervical motion restriction is necessary. The potential benefits include use as an airway adjuvant maintaining upper airway patency, reducing provider task loading. The limited research on the device efficacy and safety requires further investigation. Methods: A randomized , crossover, interventional study was performed to compare mean differences in airway patency at the level of the uvula, epiglottis, tongue and soft palate with and without the Lubo collar in awake volunteers using magnetic resonance imaging (MRI). Fourteen participants each underwent two MRI scans of the upper airway: A control scan with no Lubo collar, and an intervention scan with the Lubo collar applied and jaw thrust mechanism activated. Two independent radiologists measured anterior-posterior diameter of the airway at four anatomical levels on the resulting MRI images. Results: There was no significant difference in mean airway diameter between the control and intervention measurements at any level. Mean (SD; 95% CI: p-value) differences were 0.9 mm (-2.38; 2.3 to 0.5; p= 0.17) at the epiglottis, 0.5 mm (1.6; -0.5 to 1.4; p= 0.29) at the soft palate, 0.2 mm (2.86; -1.4 to 1.9; p = 0.78) at the tongue, 0.4 mm (4.04; -1.9 to 2.7; p = 0.72) at the uvula. Conclusion: The Lubo TM airway collar did not show a significant change in upper airway patency at four anatomical levels measured in awake adult participants. Further research is required to investigate its clinical use in patients that are unable to maintain upper airway tone. Groups of interest would include trauma, obstructive sleep apnoea, obesity and patients under general anaesthesia.